Peri‐Acenoacene for Solution Processed Distributed Feedback Laser: The Effect of 1, 2‐Oxaborine Doping. Issue 7 (21st February 2022) - Gu, Yanwei; Muñoz‐Mármol, Rafael; Fan, Wei; Han, Yi; Wu, Shaofei; Li, Zhengtao; Bonal, Víctor; Villalvilla, José M.; Quintana, José A.; Boj, Pedro G.; Díaz‐García, María A.; Wu, Jishan
Abstract: Zigzag edged nanographenes such as peri‐acenoacenes are promising materials for organic lasers, but the effects of heteroatom doping on the electronic properties and gain medium performance remain unclear. Herein, the facile synthesis of a new 1, 2‐oxaborine (BO) doped peri‐tetracenotetracene derivative, the bis(1, 2‐oxaborine)peri‐tetracenotetracene (BOTT‐Mes ), is reported. X‐ray crystallographic analysis confirms the BO‐doped planar structure and the nonexistence of intermolecular π–π stacking in solid state. Compared with the all‐carbon peri‐tetracenotetracene derivative (TT‐Ar ), the BO‐doped BOTT‐Mes exhibits more disrupted π‐conjugation at the BO sites, a lower‐lying highest occupied molecular orbital, and a larger energy gap. Due to its rigid skeleton and nonaggregative feature, it displays well‐resolved absorption and emission spectra with a small Stokes shift (8 nm) and high photoluminescence quantum yield (80%) when it is dispersed in a polystyrene (PS) thin film. Notably, 1, 2‐oxaborine doping improves the film amplified spontaneous emission (ASE) performance, with a lower ASE threshold ( E th‐ASE  = 66 µJ cm –2 ) as compared to the TT‐Ar doped PS film ( E th‐ASE  = 100 µJ cm –2 ). Furthermore, a low threshold (22 µJ cm –2 ) solution‐processed distributed feedback laser is fabricated, indicating the feasibility of using BOTT‐Mes as gain medium for practical laser applications. Abstract : Doping is better! The 1, 2‐oxaborine doped peri‐acenoacene is synthesized. It displays higher photoluminescence quantum yield and enhanced amplified spontaneous emission properties as compared to the pristine all‐carbon peri‐tetracenotetracene. Soluble processed distributed feedback laser is fabricated, showing low threshold and narrow linewidth.